Purchased of quonset huts - De La Salle University (Animo Repository, 1948)
Four quonset huts were purchased for P3,800.00 and set up on the old gym foundations for temporary quarters to house extracurricular activities, the military department, the athletic department, and the school clinic. Humphrey O'Leary, Jr., class of '34, did the hauling and erection for P4,200.00.